2010
DOI: 10.1088/0004-637x/725/1/571
|View full text |Cite
|
Sign up to set email alerts
|

EIGHT γ-RAY PULSARS DISCOVERED IN BLIND FREQUENCY SEARCHES OFFERMILAT DATA

Abstract: 10We report the discovery of eight γ-ray pulsars in blind frequency searches using the Large Area Telescope (LAT), onboard the Fermi Gamma-ray Space Telescope. Five of 1 Corresponding authors: P. M. Saz Parkinson, pablo@scipp.ucsc.edu; M. Dormody, mdormody@ucsc.edu; M. Ziegler, ziegler@scipp.ucsc.edu; P. S. Ray, Paul.Ray@nrl.navy.mil.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
164
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(169 citation statements)
references
References 39 publications
5
164
0
Order By: Relevance
“…Among the earliest scientific results from the LAT was the discovery of a large population of radio-quiet gamma-ray pulsars (Abdo et al 2009b;Saz Parkinson et al 2010), using a new blind-search technique developed specifically for the very long time series expected with the LAT (Atwood et al 2006). These findings confirmed some predictions that many of the unidentified EGRET sources in the Galactic plane were pulsars(e.g., Yadigaroglu & Romani 1995), favoring outer gap pulsar models (Cheng et al 1986;Romani 1996Romani , 2014, where the gamma rays are generated in the outer magnetosphere, as opposed to polar cap models, where the emission comes from closer to the neutron star surface(e.g., Harding & Muslimov 1998).…”
Section: Introductionmentioning
confidence: 58%
“…Among the earliest scientific results from the LAT was the discovery of a large population of radio-quiet gamma-ray pulsars (Abdo et al 2009b;Saz Parkinson et al 2010), using a new blind-search technique developed specifically for the very long time series expected with the LAT (Atwood et al 2006). These findings confirmed some predictions that many of the unidentified EGRET sources in the Galactic plane were pulsars(e.g., Yadigaroglu & Romani 1995), favoring outer gap pulsar models (Cheng et al 1986;Romani 1996Romani , 2014, where the gamma rays are generated in the outer magnetosphere, as opposed to polar cap models, where the emission comes from closer to the neutron star surface(e.g., Harding & Muslimov 1998).…”
Section: Introductionmentioning
confidence: 58%
“…If the γ -ray pulsar is located beyond 6.0 kpc, the velocity of the pulsar required for escaping from the cluster has to be as large as 3000 km s −1 or more for a characteristic age of 4.6 kyr. Saz Parkinson et al (2010) and Ackermann et al (2011) therefore suggested the distance to be 1.8-2.4 kpc.…”
Section: Introductionmentioning
confidence: 99%
“…Fujita et al (2009b) argued that the shock front of an SNR occurred in the past may have accelerated CRs and emit the TeV γ -rays by the interaction with the molecular gas toward Wd 2. Recently, Fermi collaboration discovered a γ -ray pulsar PSR J1023−5746 near the peak position of the TeV γ -ray source (Saz Parkinson et al 2010). Ackermann et al (2011) suggested that HESS J1023−575 was an associated PWN.…”
Section: Introductionmentioning
confidence: 99%
“…Among the extremes of the population of Fermi pulsars, PSR J2055+2539 (J2055 hereafter;Saz Parkinson et al 2010) is one of the best candidates. It is one of the 100 brightest γ-ray sources, with a γ-ray flux of (5.5 ± 0.1)×10 −7 erg cm −2 s −1 (Acero et al 2015).…”
Section: Introductionmentioning
confidence: 99%